FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMENUHI KEWAJIBAN PERPAJAKAN (Studi Empiris pada Pengusaha UMKM di KPP Pratama Pekanbaru Senapelan) - Resti, Vioni; Agusti, Restu; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine empirically the effect caused by the variable taxpayer compliance, taxpayer understanding, income ievel, service quality and confidence in the legal system and government on the small, and Medium entrepreneurs in KPP Pratama Pekanbaru Senapelan. This study uses accidental sampling with 96 samples obtained from the calculation formula slovin. Data collection techniques in this study is in the form of questionnaires, while data analysis technique used is multiple regression analysis were processed with SPSS version 20 for Windows. From the results of the testing that has been done, simultaneous regression test (F test) showed that all independent variables studied have a simultaneous effect on the variable taxpayer compliance. Partial regression test (t test) indicates that the variables taxpayer understanding, service quality, income level and confidence in the legal system and government effect on tax compliance. The magnitude of the effect caused by the Adjusted R2 by four variables together on the dependent variable 38,8%, while the remaining 61,2% is the effect by other variables not examined in this study.Keywords : tax compliance, understanding of the taxpayer, service quality, income level, confidence in the legal system and government